Reaksi Pasar Perusahaan yang Terdaftar di Bursa Efek Indonesia terhadap Pengumuman Stock Buyback di Tahun 2020 – 2021 - Narry Rahmawati; Muhammad Roni Indarto (Sekolah Tinggi Ilmu Manajemen YKPN Yogyakarta, 2022)
The purpose of this study is to determine whether there is a difference between the average abnormal return and the average trading volume activity before and after the announcement of the share buyback. The sample used in this study was 38 companies listed on the Indonesia Stock Exchange (IDX) in 2020-2021 with a sampling technique using purposive sampling. This research is an event study with a window period of 11 days (5 days before, 1 day of the event, and 5 days after). The analytical method used is descriptive statistics and paired sample t-test. The results showed that there was no difference in the average abnormal return before and after the announcement of the share buyback and there was a difference in the average trading volume activity before and after the announcement of the share buyback.